(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The effective use of information technology in the learning process is an important factor in the organization of the educational process. The use of information technology at different stages of the lesson activates mental processes: perception, attention, memory, thinking. Explaining new material using presentations as a source of educational information optimizes the learning process. Thus, the use of information technology in education has ample opportunities. The constant growth of the level of information and communication technologies entails an increase in potential opportunities for educational purposes, which in turn are successfully implemented and used in practice.